2013
DOI: 10.7585/kjps.2013.17.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Pre-Harvest Residue Limit (PHRL) of Methoxyfenozide and Novaluron on Peaches

Abstract: Methoxyfenozide and novaluron were sprayed with single and triple treatments separately on peach during cultivation period. Samples were collected over 14 days, 8 times in total (0, 2, 4, 6, 8, 10, 12, 14 days). Methoxyfenozide and novaluron were extracted with acetone and partitioned with dichloromethane, and analyzed by HPLC/DAD. Method Quantitation Limit (MQL) were both 0.005 mg/kg, average recoveries of methoxyfenozide at two fortification levels of 0.05 and 0.25 mg/kg were determined 92.7±2.9% and 102.8±3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Besides, t 1/2 varies with the type of plant as well. The t 1/2 of methoxyfenozide in cauliflower is similar to that in Chinese cabbage 11 but shorter than that in peaches 12 and grape. 13 In the present study, the t 1/2 in tea shoots (1.2 days) is shorter than that in cauliflower (2.5-3.5 days), though the initial residue in tea shoots (12.9 mg kg −1 ) is much higher than that in cauliflower (0.14-4.38 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Besides, t 1/2 varies with the type of plant as well. The t 1/2 of methoxyfenozide in cauliflower is similar to that in Chinese cabbage 11 but shorter than that in peaches 12 and grape. 13 In the present study, the t 1/2 in tea shoots (1.2 days) is shorter than that in cauliflower (2.5-3.5 days), though the initial residue in tea shoots (12.9 mg kg −1 ) is much higher than that in cauliflower (0.14-4.38 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 54%
“…Lee et al 11 studied the residual characteristic of methoxyfenozide and found that its half-life in Chinese cabbage was 3.5 days. Cho et al 12 reported that the half-life of methoxyfenozide in peaches was 4.4 days at single treatment and 4.2 days at triple treatment. Kim et al 13 revealed that the half-life of methoxyfenozide was 5.1-6.1 days in grape.…”
Section: Introductionmentioning
confidence: 99%